Long-term benefit of vasodilating beta-blockers in acute myocardial infarction patients with mildly reduced left ventricular ejection fraction - Ki Yung Boo; Miyeon Kim; Jae-Geun Lee; Geum Ko; Joon Hyouk Choi; Song-Yi Kim; Seung-Jae Joo; Jin-Yong Hwang; Seung-Ho Hur; Kwang Soo Cha; Myung Ho Jeong (PLoS ONE, 2025)
Beta-blockers have been considered the cornerstone of treatment for patients with acute myocardial infarction (AMI). However, long-term benefits of vasodilating beta-blockers remain uncertain. This study aimed to investigate the long-term clinical benefits of vasodilating beta-blockers compared to conventional beta-blockers in AMI patients with mildly reduced ejection fraction (mrEF). Among 13,624 patients who enrolled in the nationwide AMI database of South Korea, the KAMIR-NIH Registry, 2,662 AMI patients with mrEF, who were prescribed beta-blockers at discharge were selected for this study. The primary outcome was a composite of cardiac death, recurrent MI, or hospitalization for heart failure (HF) during 3-year follow up period. In the entire cohort, the use of vasodilating beta-blockers at discharge was associated with lower incidence of primary outcome at 3-year (hazard ratio [HR] 0.80; 95% confidence interval [CI], 0.62–0.98; P = 0.039) compared to the use of conventional beta-blockers at discharge. In the propensity score–matched (PSM) cohort, the use of vasodilating beta-blockers at discharge was also associated with a significantly lower incidence of primary outcome (HR, 0.66; 95% CI, 0.50–0.88; P = 0.004) compared to the use of conventional beta-blockers at discharge. Furthermore, in the PSM cohort, the use of vasodilating beta-blockers was associated with lower incidences of the cardiac death (HR, 0.60; 95% CI, 0.39–0.92; P = 0.020), hospitalization for HF (HR, 0.72; 95% CI, 0.46–0.98; P = 0.042), and all-cause death (HR, 0.67; 95% CI, 0.48–0.93; P = 0.017) compared to the use of conventional beta-blockers. However, no significant differences were observed between the groups in the incidences of recurrent MI (HR, 0.62; 95% CI, 0.34–1.14; P = 0.122), any revascularization (HR, 1.04; 95% CI, 0.76–1.42; P = 0.821), stroke (HR, 0.84; 95% CI, 0.44–1.60; P = 0.589), stent thrombosis (HR, 1.12; 95% CI, 0.40–3.11; P = 0.833). In AMI patients with mrEF, the use of vasodilating beta-blockers at discharge was associated with better long-term clinical outcomes compared to the use of conventional beta-blockers.